2022
DOI: 10.1007/s10792-022-02515-y
|View full text |Cite
|
Sign up to set email alerts
|

Infectious keratitis caused by Klebsiella spp.: predisposing factors, presentation, and management

Abstract: To study predisposing factors, clinical presentation and management strategies for klebsiella keratitis. MethodsA retrospective case review was performed on clinical records of culture-proven klebsiella keratitis cases in a tertiary referral center over an 8-year period (from 2012 to 2020). ResultsThirty eight episodes of culture-proven klebsiella keratitis were identi ed in 37 patients. The mean age of the patients was 62.9 years (range, 24-101).. Multiple predisposing factors were identi ed in 33 eyes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…While Masoumi A and his group in a study of thirty eight cases of culture-proven klebsiella keratitis were identified in 37 patients. They identified Multiple predisposing factors; 33 eyes with history of ocular trauma (7 cases), preexisting ocular surface disease (7 cases) and diabetes (6 cases) history of previous keratoplasty (11 cases) [19]. In the study of Laspina,F and his group approximately half of cases had a history of trauma, the other half of these involved foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…While Masoumi A and his group in a study of thirty eight cases of culture-proven klebsiella keratitis were identified in 37 patients. They identified Multiple predisposing factors; 33 eyes with history of ocular trauma (7 cases), preexisting ocular surface disease (7 cases) and diabetes (6 cases) history of previous keratoplasty (11 cases) [19]. In the study of Laspina,F and his group approximately half of cases had a history of trauma, the other half of these involved foreign bodies.…”
Section: Discussionmentioning
confidence: 99%